CRISPRi Induced Suppression of Fimbriae Gene (fimH) of a Uropathogenic Escherichia coli: An Approach to Inhibit Microbial Biofilms - Zuberi, Azna; Ahmad, Nayeem; Khan, Asad U. (Frontiers in Immunology, 2017)
Urinary tract infection is one the common infections caused by the recalcitrant nature of biofilms, developed after the pathogen has adhered to the inner lining of the urinary tract. Although significant research has been made in recent years to control these types of infection, but as of yet, no approach has sufficiently been able to reduce the prevalence of UTIs. The main objective of this study was to prevent UTIs through targeting the fimH gene, which is the major virulent factor responsible for biofilm formation. The novelty of this work lies in the use of CRISPRi, a gene specific editing tool to control such types of infections. Accordingly, the system was designed to target fimH gene, responsible for bacterial adherence and this approach was successfully validated by performing microscopic, biofilm and adherence assays.